Formulating Urban Design Guidelines for Optimum Carrying Capacity of a Place. (2016) - George, Roshni Maria; Kumar Kini, Manoj
Abstract: "Growth is inevitable and desirable, but destruction of community character is not. The question is not whether your part of the world is going to change. The question is how." -Edward T. McMahon We live in a world of uncontrolled development and depleting resources. There is growing concern about the consumption of precious resources and various efforts to conserve it. But these efforts are often unproductive. One of the reasons for this is unplanned consumption and development. Architects and urban designers are especially challenged as they are a group of professionals who contribute to such mishaps. There is a need to limit such development. This study aims at estimating such limits by optimizing carrying capacity of a place and suggesting guidelines for sustainable development.